PERLINDUNGAN HUKUM TERHADAP PEMBANTU RUMAH TANGGA DI PROPINSI SUMATERA UTARA - Hanifah, Ida; -, Ramlan; -, Harisman (MEDIA HUKUM, 2014)
The Presence of maid servants in this modern time are needed very much by a lot of people, especially for the cityzenshios. In working the servants sometimes get the unconfortable teatments like the other workers. The maid servants have to be able to de many houses works, no limit times and get the low wages, and very often are treated as the masters like (the hosts of the houses). These bad conditions are very often hidden result of low loegal protections that are given to the maid servants, mainly that related to the fulfilment of normative rights of workers as being valid usually.